1997
DOI: 10.1136/fn.76.3.f179
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patent ductus arteriosus with ibuprofen

Abstract: Aim-To evaluate the eYciency and side eVects of ibuprofen for the early treatment of patent ductus arteriosus (PDA)and compare it with indomethacin. Methods-Forty preterm infants with gestational ages of less than 33 weeks, with respiratory distress syndrome (RDS) and echocardiographically confirmed PDA, were randomly assigned at days 2 to 3 of life to receive either intravenous indomethacin 3 × 0.2 mg/kg at 12 hour intervals or intravenous ibuprofen 1 × 10 mg/kg, followed by 5 mg/kg 24 and 48 hours later. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
3
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 36 publications
10
97
3
8
Order By: Relevance
“…In two trials (5,6), the proportion of infants who developed chronic lung disease was significantly higher with ibuprofen than with indomethacin. Furthermore, ibuprofen is 99% protein bound, and in vitro studies suggest that it may displace bilirubin from albuminbinding sites, thereby increasing the risk for kernicterus (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two trials (5,6), the proportion of infants who developed chronic lung disease was significantly higher with ibuprofen than with indomethacin. Furthermore, ibuprofen is 99% protein bound, and in vitro studies suggest that it may displace bilirubin from albuminbinding sites, thereby increasing the risk for kernicterus (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Because it purportedly lacks these side effects, ibuprofen has been proposed as a pharmacologically similar, but therapeutically preferential alternative in the treatment of PDA (5)(6)(7)(8)(9)(10)(11). Ibuprofen is also a cyclooxygenase inhibitor, which seems to be equally effective in mediating ductal closure, while minimizing adverse renal effects (11).…”
mentioning
confidence: 99%
“…Search results and citation lists for prior publications identified 75 randomized-controlled trials of interventions that close a PDA in preterm infants. In 26 trials (five comparing long and short courses of indomethacin, [37][38][39][40][41] 19 comparing indomethacin and ibuprofen, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and two that included very early crossover to treatment of nonresponders 29,61 ), rates of ductal closure did not differ between treatment assignments, precluding evaluation of effects of ductal closure on other outcomes, so these were excluded. The remaining 49 trials, 36, including 4728 subjects, were deemed potentially informative, as all but one documented substantial reduction in ductal patency after treatment.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Published trials have also demonstrated its better safety and tolerability as compared to indomethacin and its possible role in neonatal therapeutics. [11][12][13] Since the first report of drug-bilirubin interactions in the pathogenesis of kernicterus, the potential for significant drug-bilirubin interactions has become an important consideration in neonatal drug therapy.…”
Section: Introductionmentioning
confidence: 99%